The Integration of the Program Evaluation Standards into an Evaluation Toolkit for a Transformative Model of Care for Mental Health Service Delivery - M. Elizabeth Snow; Mai Berger; Alexia Jaouich; Mélanie Hood; Amy Salmon (Journal of MultiDisciplinary Evaluation, 2023)
Background: Stepped Care 2.0 (SC2.0) is a transformative model of mental health service delivery. This model was created by Stepped Care Solutions (SCS), a not-for-profit consultancy that collaborates with governments, public service organizations, and other institutions that wish to redesign their mental health and addictions systems of care. The SC2.0 model is based on 10 foundational principles and 9 core components that can be flexibly adapted to an organization’s or community’s needs. The model supports groups to reorganize and deliver mental health care in an evidence-informed, person-centric way. SCS partnered with evaluators from the Centre for Health Evaluation and Outcome Sciences (CHÉOS) to create a toolkit that provides evaluation guidance. The toolkit includes a theory of change, guidance on selecting evaluation questions and designs, and an evaluation matrix including suggested process and outcome metrics, all of which can be tailored to each unique implementation of the SC2.0 model. The objective of this resource is to support organizations and communities to conduct high-quality evaluations for the purpose of continuous improvement (a core component of the model of care) and to assess the model’s impact.